Repercussions of depression in pregnancy in mothers and children: a systematic review - de Oliveira Pimentel Lima, Marlise; Tsunechiro, Maria Alice (O Mundo da Saúde, 2008)
The present article had as its aim to identify repercussions of depression in pregnancy in obstetric, perinatal outcomes in the posterior life of mother and child, according to the literature. We carried through a systematic review of research article in databases Lilacs, Medline, Cinahl and Pubmed, about perinatal repercussions of depression in pregnancy in mothers and newborns, considering the period 1999 to February 2008. 33 papers were included. Most studies were carried through in developed countries (90.9%). For the woman, the main repercussions are alterations in quality of life related to health and in health practices complications in gestation, being depression in the gestation the risk factor for puerperal depression, preeclampsia, premature childbirth, mainly in pregnant women of low socioeconomic condition. For the embryo/child, the main repercussions had been the rise of norepinephrine and cortisol, low weight at birth, being born under gestational age, sleep troubles and compromised development up to three years of age.